Gender and East Asian Welfare States: from Confucianism to Gender Equality - Pascall, Gillian; Sung, Sirin (2007)
How can we understand the gender logic underpinning the welfare states/systems of East Asia? Does the comparative literature, which has largely been concerned with western Welfare states, whether in The Three Worlds of Welfare Capitalism (Esping-Andersen 1990), or in gender-based analysis of the male breadwinner model (Lewis 1992, 2001, 2006), have anything to offer in understanding the gender assumptions underpinning East Asian welfare states? Are the welfare systems of East Asian countries distinctive, with Confucian assumptions hidden beneath the surface commitment to gender equality? We will use the (mainly western) comparative literature, but argue that Confucian influences remain important, with strong assumptions of family, market and voluntary sector responsibility rather than state responsibility, strong expectations of women’s obligations, without compensating rights, a hierarchy of gender and age, and a highly distinctive, vertical family structure, in which women are subject to parents-in-law. In rapidly changing economies, these social characteristics are changing too. But they still put powerful pressures on women to conform to expectations about care, while weakening their rights to security and support. Nowhere do welfare states’ promises bring gender equality in practice. Even in Scandinavian countries women earn less, care more, and have less power than men. We shall compare East Asian countries (Japan, Korea, Taiwan where possible) with some Western ones, to argue that some major comparative data (e.g. OECD) show the extreme situation of women in these countries. Some fine new qualitative studies give us a close insight into the experience of mothers, including lone and married mothers, which help us to understand how far the gender assumptions of welfare states are from Scandinavia’s dual earner model. There are signs of change in society as well as in economy, and room for optimism that women’s involvement in social movements and academic enquiry may be challenging Confucian gender hierarchies.